Answer:
The solution to the inequality is:
![-1\le \:x\le \:3](https://img.qammunity.org/2022/formulas/mathematics/high-school/hi4900mt9tciffwugqipkc9rb1z8jmj6xw.png)
The line graph of the solution is also attached.
Explanation:
Given the expression
![4x-1\:\le \:5x\:\le \:3\left(x+2\right)](https://img.qammunity.org/2022/formulas/mathematics/high-school/wkpg2ei8zqsygqh9rrohl57xy5tx8ij10h.png)
solving the expression
![4x-1\:\le \:5x\:\le \:3\left(x+2\right)](https://img.qammunity.org/2022/formulas/mathematics/high-school/wkpg2ei8zqsygqh9rrohl57xy5tx8ij10h.png)
![4x-1\le \:5x\quad \mathrm{and}\quad \:5x\le \:3\left(x+2\right)](https://img.qammunity.org/2022/formulas/mathematics/high-school/bvhqwueqwruch949kout60v5cl1mcpm4yv.png)
solving
![4x-1\le \:5x](https://img.qammunity.org/2022/formulas/mathematics/high-school/ao2q4fyh8cd3eteyfj7lznjkcm6mry0kex.png)
Add 1 to both sides
![4x-1+1\le \:5x+1](https://img.qammunity.org/2022/formulas/mathematics/high-school/3fkuch8movzhjdiaaxindc22igv2yzw7ju.png)
Simplify
![4x\le \:5x+1](https://img.qammunity.org/2022/formulas/mathematics/high-school/vogt0i6zgiby9zyzxxjs96z6qfhof3b2ha.png)
Subtract 5x from both sides
![4x-5x\le \:5x+1-5x](https://img.qammunity.org/2022/formulas/mathematics/high-school/smttlh9csaag5p1wws8pzgvdzo94ve3m62.png)
simplify
![-x\le \:1](https://img.qammunity.org/2022/formulas/mathematics/high-school/hopajkofye7dykm8cszwrbam4m1knbg8uo.png)
Multiply both sides by -1 (reverse inequality)
![\left(-x\right)\left(-1\right)\ge \:1\cdot \left(-1\right)](https://img.qammunity.org/2022/formulas/mathematics/high-school/3zgvfz2dwi8myy2ycrkqxlfz2emmvbnqe1.png)
Simplify
![x\ge \:-1](https://img.qammunity.org/2022/formulas/mathematics/high-school/u573zxlwiegzs2e2ec896bq5qfrjo87jhb.png)
Similarly solving
![5x\le \:3\left(x+2\right)](https://img.qammunity.org/2022/formulas/mathematics/high-school/tasd1k2ws98cfk5x1muqb5yap3stxhvkvs.png)
Subtract 3x from both sides
![5x-3x\le \:3x+6-3x](https://img.qammunity.org/2022/formulas/mathematics/high-school/1zbu8oxnxkovgh1fk6f4ocf5yo5jf8l9uy.png)
Simplify
![2x\le \:6](https://img.qammunity.org/2022/formulas/mathematics/high-school/5bt2x8pqbcx3lu3f72kgyy8a78clytz0mt.png)
Divide both sides by 2
![(2x)/(2)\le (6)/(2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/xt6vcbj2yxsilb77o3frlkhpnal7swah2k.png)
Simplify
![x\le \:3](https://img.qammunity.org/2022/formulas/mathematics/high-school/5oq6euogen1feyca0udtb192xj4n5nugln.png)
So combine the interval
![x\ge \:-1\quad \mathrm{and}\quad \:x\le \:3](https://img.qammunity.org/2022/formulas/mathematics/high-school/thze76uzqad89uzhro1xrmyne0lzgbfsqx.png)
Merge overlapping intervals
![-1\le \:x\le \:3](https://img.qammunity.org/2022/formulas/mathematics/high-school/hi4900mt9tciffwugqipkc9rb1z8jmj6xw.png)
Therefore, the solution to the inequality is:
![-1\le \:x\le \:3](https://img.qammunity.org/2022/formulas/mathematics/high-school/hi4900mt9tciffwugqipkc9rb1z8jmj6xw.png)
The line graph of the solution is also attached.